1999
DOI: 10.1007/s004420050928
|View full text |Cite
|
Sign up to set email alerts
|

Top-down effects of insect herbivores during early succession: influence on biomass and plant dominance

Abstract: We tested the hypothesis that phytophagous insects would have a strong top-down effect on early successional plant communities and would thus alter the course of succession. To test this hypothesis, we suppressed above-ground insects at regular intervals with a broad-spectrum insecticide through the first 3 years of old-field succession at three widely scattered locations in central New York State. Insect herbivory substantially reduced total plant biomass to a similar degree at all three sites by reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
104
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 86 publications
5
104
1
2
Order By: Relevance
“…In early old-field succession in the USA, Carson & Root (1999) found in insect exclusion experiments that insects consistently suppressed plant biomass and changed the relative abundance of species across all three study-sites by the third year of succession. The effect of insects can be attributed almost entirely to one insect species, the cosmopolitan and highly polyphagous meadow spittlebug Philaenus spumarius, which made up 68-94% of the entire herbivore load in the pivotal third year of succession.…”
Section: Paradigms Lost Paradigms Gainedmentioning
confidence: 86%
See 1 more Smart Citation
“…In early old-field succession in the USA, Carson & Root (1999) found in insect exclusion experiments that insects consistently suppressed plant biomass and changed the relative abundance of species across all three study-sites by the third year of succession. The effect of insects can be attributed almost entirely to one insect species, the cosmopolitan and highly polyphagous meadow spittlebug Philaenus spumarius, which made up 68-94% of the entire herbivore load in the pivotal third year of succession.…”
Section: Paradigms Lost Paradigms Gainedmentioning
confidence: 86%
“…Preference for the symmetrical view may reflect belief in a balance of nature, or it may represent a logical starting point for theoretical models of ecological and coevolutionary dynamics of herbivore-plant, predator-prey, and parasite-host population interactions. More substantively, a growing number of ecological studies have demonstrated that removing herbivores or pathogens often increases plant population size or plant fitness (Bigger & Marvier, 1998;Marquis, 1992), alters the pattern of selection on genetic variation in chemical and morphological characters that have been shown to reduce herbivore damage on plants in the field (Mauricio & Rausher, 1997), and changes the speed and direction of ecological succession (Bach, 2001;Brown & Gange, 1992;Carson & Root, 1999;Fagan & Bishop, 2000). These findings bolster the assumption that insect herbivores impose strong negative effects on plants and support the symmetrical view that insects and plants exert major effects on each other.…”
Section: Introductionmentioning
confidence: 99%
“…Other theories on how herbivores can promote coexistence require a trade-off between the vigorous growth of plants and their defense against consumers, assuming that defense is costly and constrains investment in other important traits (Coley et al 1985, Herms and Mattson 1992, Viola et al 2010, Kempel et al 2011, Lind et al 2013. If the plants growing most vigorously in a community are also the least defended ones, herbivores promote coexistence by selectively feeding on more vigorously growing and hence less defended plant species (Pacala andCrawley 1992, Carson andRoot 1999), thereby reducing average fitness differences between species, which is considered as an equalizing mechanism (Chesson 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among the insect guilds, the herbivores have an important role in maintaining the diversity and energy flow (Janzen, 1987;Mulder et al, 1999;Belovsky and Slade, 2003;Carson and Root, 2009). Herbivores may prevent high recruitment rates of some plant species allowing coexistence of higher arboreal species diversity in tropical forests (Janzen, 1970;Connell et al, 1984).…”
Section: Introductionmentioning
confidence: 99%